COVID-19 PANDEMIC AND DEVELOPMENT OF CONSPIRACY THEORIES IN COMMUNITY: PSYCHIATRIC ASPECT OF CONSPIRACY THEORIES - Ismail Afandi Kalam; Zuhrotun Ulya (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2020)
ABSTRACTCoronavirus Disease 2019 or COVID-19 first appeared at the end of 2019 in Wuhan, China, and spread across the world, and declared as pandemic at Mach 11th, 2020. Rapid increasing of cases and mortality rate accompanied by less understanding of the disease causing anxiety and fear among people. Conspiracy theory is a baseless belief that there are enormous and evil power planning for massive events for hidden and evil intention. Conspiracy theory associated with anxiety and lack of control faced by individual. Conspiracy theory is a mechanism to giving a simple explanation of a condition to rationalize an event, with the aim to make people feel safe and secure inside their environment, and giving feel of control their environment. Conspiracy theory also associated with paranoia, paranoid idea, schizotypal personality, and belief of paranormal phenomenon. Conspiracy theory can cause certain individual behavior in handling COVID-19, based on theory that they believe in.Kata Kunci: Conspiracy theory, COVID-19, anxiety, paranoia, paranoid idea, schizotypal